2022
DOI: 10.5603/rpor.a2022.0078
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for post-recurrence survival among patients with locally advanced cervical cancer who underwent definitive concurrent chemoradiation

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…According to the Pitchaya Thongkhao’s 2022 report, which analyzed 1658 patients with locally advanced cervical cancer undergoing concurrent chemoradiation therapy with brachytherapy based on point A, it was found that roughly 75% of recurrence cases occurred within two years after completing treatment, and an approximate locoregional recurrence rate of 18% [ 21 ]. With a median follow-up time of 19 months, we observed 3 cases of locoregional recurrence (accounting for 4.2%) and the locoregional control rate in our study was 95.8%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Pitchaya Thongkhao’s 2022 report, which analyzed 1658 patients with locally advanced cervical cancer undergoing concurrent chemoradiation therapy with brachytherapy based on point A, it was found that roughly 75% of recurrence cases occurred within two years after completing treatment, and an approximate locoregional recurrence rate of 18% [ 21 ]. With a median follow-up time of 19 months, we observed 3 cases of locoregional recurrence (accounting for 4.2%) and the locoregional control rate in our study was 95.8%.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies reporting that pretreatment hemoglobin level, leukocyte, and platelet counts are associated with the prognosis of locally advanced cervical cancer patients undergoing CCRT. 48 , 49 After using the CCRT-nomogram to predict the probability that individual patient is suitable to receive CCRT, the prognostic nomogram could effectively predict the prognosis of newly diagnosed mCC patients. However, the administration of CCRT in this study was affected by human subjective factors, and the model should be validated with larger samples and in prospective study.…”
Section: Discussionmentioning
confidence: 99%